PENGARUH LINGKUNGAN KERJA DAN KOMUNIKASI ORGANISASI TERHADAP KEPUASAN KERJA GURU PADA SMPN 1 BANUHAMPU KABUPATEN AGAM - Husna, Nikmatul (journal of residu, 2019)
The purpose of this research is to identify and analyze the influence of work environment and organizational communication toward the satisfaction of teachers’ work  in SMPN 1 Banuhampu Kabupaten Agam. The population of the research is the teachers in SMPN 1 Banuhampu Kabupaten Agam. Samples taken are 56 respondents by using random sampling technique,  which determine  samples by taking a sample randomly and use the questionnaire as a tool to collect data. Based on hypothesis  in this research, it is assumed that the influence of work environment and organizational communication significantly and positively influence the teachers’ work satisfaction  in SMPN 1 Banuhampu Kabupaten Agam. The data analysis methods author used in this research are validity tes, reliability test, variable descriptive analysis test, classical assumtion tes,multiple linear regression analysis, T test and F test. From analysis that have been done, author found that work environment variable (X1) is significantly and positively influence the satisfaction of teachers’ work, this is proven by the significant probability value of work environment is resulted in 0,000 which is smaller than 0,05. Then author also found that effect of organizational communication variable (X2) toward the work satisfaction is significantly and positively influence the teachers’ work, this is proven by significant probability value of communication organization is resulted in 0,000 which is smaller than 0,05. From F test, it can be concluded that regression model can be use to predict the work environment and organizational communication which have  significantly and  positively  influence toward teachers’ work satisfaction by the significant probability value is resulted in 0,000 which is smaller than 0,05.